PENDIDIKAN MULTIKULTURALISME SEBAGAI STRATEGI PENGEMBANGAN POTENSI MANUSIA UNTUK MENGHARGAI PLURALITAS - Ola Rongan Wilhelmus (Bahasa Indonesia, 2018)
Differences in language, customs, and culture in Indonesian society are reality that can not be denied. It is indeed recognized by the Indonesian nation, and will continue to happen since past, present and in times to come. The diversity of the people of Indonesia can be a blessing because it brings extraordinary cultural richness. This cultural wealth wisely when processed will be a beautiful mosaic and the force of national nasional.Kekuatan is not only necessary to strengthen the unity of the nation but also to provide a similar, equal, and fair for everyone, communities and cultures in Indonesia to participate actively in the development of the country and nation. This paper was written to discuss the nature of multiculturalism, the potential power and social conflicts are rooted in the problems of multiculturalism, as well as education multikulturalism as a national strategy to give understanding, understanding and experience of the people and the Indonesian people about the significance of the spirit of togetherness, mutual respect, mutual love, mutual tolerance and mutual understanding between each other, although different in race, ethnicity, race, culture, religion and beliefs.